Female Sympathisers of ISIS as Muhajirahs in ISIS-Affiliated Media - Ungku Mohd Nordin, Ungku Khairunnisa; Surinderpal Kaur (Journal of Modern Languages, 2022)
International media have reported on the Islamic State of Iraq and Al-Sham (ISIS), an international terrorist organisation based in Syria and Iraq since 2014. Women, often young and unmarried, were leaving their homes and families to sneak into Syria and join ISIS, according to reports in the international media (Neumann, 2015). Sjoberg &Gentry (2011) assert that the media’s portrayal of female terrorists and the factors that encourage women to support terrorist organisations have not been sufficiently investigated. This study examines the discursive strategies employed by ISIS-affiliated media outlets to represent female sympathisers as muhajirahs. Using Critical Discourse Analysis – the Discourse Historical Approach (Resigl, 2017), this paper will analyse the diverse and often contested ways in which the Self versus Other (Wodak, 2009) schemata is prominent in the representations of ISIS female sympathisers. The data were taken from ISIS-affiliated media, including the Manifesto from the Al Khannssa Brigade and six Dabiq magazines. This paper will focus on referential, predicational and argumentation strategies (topoi) in the selected ISIS-affiliated media. This paper intends to pave the way for an examination of gender and terrorism that explores the complexities of representations by examining gender through multiple lenses.